Analisis Kepuasan Pengguna WhatsApp Web Menggunakan Metode Webqual 4.0 dan IPA - Andry, Johanes Fernandes; -, Herlina; Angelina, Vern Jessica (JURNAL FASILKOM, 2023)
Social media has become a lifestyle that cannot be ignored in recent times. One of the most frequently used online communication tools today is WhatsApp, which was created in 2009 by Jan Koum. In Indonesia, this application is used by all groups ranging from young and old, students to workers / employees who indirectly WhatsApp is a social media that has many advantages to become quite important in everyday life in society. The emergence of WhatsApp Web is a technology that gives its users the freedom to use more than one device, so that it can attract more users to use it. With so many users, researchers want to know how user satisfaction from this website regarding its usability, appearance, and service quality. Of course, to analyze the research, several methods are needed so that the analysis can run well. This research integrates the WebQual 4.0 and Importance Performance Analysis methods as a data analysis process. Researchers also used a questionnaire as a way to collect data from WhatsApp Web users, the questionnaire consisted of 23 questions with two indicators of expectations and performance. The results of this study are that there is a good influence from Usability Quality and Services Interaction Quality on user satisfaction and another case with Information Quality which has no effect. The recommendation for users is that WhatsApp Web cannot be accessed via a browser on a PC or laptop, it is possible that there is a VPN (Virtual Private Network) application, this application must be deactivated first.